2011
DOI: 10.1248/bpb.34.1143
|View full text |Cite
|
Sign up to set email alerts
|

Xanthine Oxidase Inhibitory Activities and Crystal Structures of Methoxyflavones from Kaempferia parviflora Rhizome

Abstract: Kaempferia parviflora (KP), a Zingiberaceae plant, is used as a folk medicine in Thailand for the treatment of various symptoms, including general pains, colic gastrointestinal disorders, and male impotence. In this study, the inhibitory activities of KP against xanthine oxidase (XOD) were investigated. The extract of KP rhizomes showed more potent inhibitory activity (38% at 500 m mg/ml) than those of the other Zingiberaceae plants tested. Ten methoxyflavones were isolated from the KP extract as the major che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Its rhizome has been used in folk medicine reportedly for health promotion and stimulation. Several pharmacological responses to KP and its components have been claimed, including aphrodisiac (Sudwan et al, 2006;Wattanapitayakul et al, 2007;Chaturapanich et al, 2008;Wattanathorn et al, 2012), antipeptic ulcer (Rujjanawate et al, 2005), anti-inflammatory Sae-wong et al, 2009;Nakao et al, 2011), antiallergenic , antimutagenic (Azuma et al, 2011), antidepressive (Wattanathorn et al, 2007), antimicrobial (Yenjai et al, 2004Kummee et al, 2008), anticholinesterase (Sawasdee et al, 2009), anticancer (Wen et al, 2005;Banjerdpongchai et al, 2008;Leardkamolkarn et al, 2009;Wudtiwai et al, 2011), cardioprotective (Tep-areenan et al, 2010;Malakul et al, 2011a,b), and antiobesity activity (Akase et al, 2011). In addition, inhibition of P-glycoprotein function and multidrug resistance-associated protein by KP have been demonstrated (Patanasethanont et al, 2007a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Its rhizome has been used in folk medicine reportedly for health promotion and stimulation. Several pharmacological responses to KP and its components have been claimed, including aphrodisiac (Sudwan et al, 2006;Wattanapitayakul et al, 2007;Chaturapanich et al, 2008;Wattanathorn et al, 2012), antipeptic ulcer (Rujjanawate et al, 2005), anti-inflammatory Sae-wong et al, 2009;Nakao et al, 2011), antiallergenic , antimutagenic (Azuma et al, 2011), antidepressive (Wattanathorn et al, 2007), antimicrobial (Yenjai et al, 2004Kummee et al, 2008), anticholinesterase (Sawasdee et al, 2009), anticancer (Wen et al, 2005;Banjerdpongchai et al, 2008;Leardkamolkarn et al, 2009;Wudtiwai et al, 2011), cardioprotective (Tep-areenan et al, 2010;Malakul et al, 2011a,b), and antiobesity activity (Akase et al, 2011). In addition, inhibition of P-glycoprotein function and multidrug resistance-associated protein by KP have been demonstrated (Patanasethanont et al, 2007a,b).…”
Section: Introductionmentioning
confidence: 99%
“…The major chemical components isolated from the extract were methoxyflavones ( 81–82) with mixed‐type mode of inhibition (Fig. ) . Bustanji and colleagues evaluated Jordanian medicinal plants extracts for XO inhibitory potential.…”
Section: Xanthine Oxidasementioning
confidence: 99%
“…Saewung et al (2009) (5) had also demonstrated that an ethanolic extract of K. parviflora markedly inhibited PGE 2 release and suppressed mRNA expression of iNOS in dosedependent manners, whereas COX-2 mRNA expression was partly affected. Furthermore, ten methoxyflavones were isolated from K. parviflora extract and PMF and 5,7,3'4'-tetramethoxyflavone showed inhibitory xanthine oxidase activity (6). With its strong anti-inflammatory effect, several K. parviflora products are available in the market including pills, capsules, tea, and wine.…”
Section: Introductionmentioning
confidence: 99%